2017
DOI: 10.1007/s00427-017-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of duplicated snail genes in the leech Helobdella

Abstract: snail gene family members are zinc-finger transcription factors with key roles in morphogenesis. Involvement of snail family genes in mesoderm formation has been observed in insects and mammals. The snail genes are also involved in cell motility, neural differentiation, cell fate, survival decision, and left-right identity. The functions of snail genes have been studied primarily among ecdysozoans and deuterostomes, with relatively little work carried out in lophotrochozoans. In this study, we isolated two sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is formed by the dynamic organization of the micromere originating from the mesodermal DM cell to form the complex muscle structure in the proboscis [19]. During formation, the proboscis develops under the control of various transcription factors and signal pathways such as Twist, Hedgehog (hh), and Snail [20,21,22]. Among the numerous signal factors, Hedgehog, known as the segment polarity factor, is associated with organogenesis in the leech and plays a major role in the development of the proboscis [20].…”
Section: Resultsmentioning
confidence: 99%
“…It is formed by the dynamic organization of the micromere originating from the mesodermal DM cell to form the complex muscle structure in the proboscis [19]. During formation, the proboscis develops under the control of various transcription factors and signal pathways such as Twist, Hedgehog (hh), and Snail [20,21,22]. Among the numerous signal factors, Hedgehog, known as the segment polarity factor, is associated with organogenesis in the leech and plays a major role in the development of the proboscis [20].…”
Section: Resultsmentioning
confidence: 99%
“…E : arid; protein sequences from H. sapiens MRF1 and MRF2 were used as outgroups (Wilsker et al, ). F : snail; protein sequences from S. kowalevskii and M. musculus scratch were used for the outgroup (Kim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Because Cfo‐snail2a and Cfo‐snail2b show different expression patterns, they likely fulfill distinct roles in ectomesodermal development, and functional studies will be needed to decipher their exact roles. Dual snail homologs are commonly found in spiralians, including the molluscs Patella (Lespinet et al, ) and Lottia gigantia (Kerner et al, ), the polychaete annelids Capitella (Dill et al, ) and Platynereis (Kerner et al, ), and in leeches (Goldstein et al, ; Kutschera et al, ; Kim et al, ). Evidence suggests that these homologs are not rooted in a single, common duplication within the Lophotrochozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, many studies have been performed to understand the develpomental involvement of various transcription factors [26][27][28] and signalling molecules [29][30][31], including physiological substances in the anterior region of the leech [32]. Previous studies have suggested that anterior development involves a combination of numerous signalling pathways and transcription factors and that the anterior head is a vast hub of gene expression.…”
Section: Introductionmentioning
confidence: 99%